Aligning Research with Islamic Ethics: Navigating the Challenges of LGBT and Sexual Education Research in Academic Inquiry - Mohammed Rasheedan, Ellin; Siti Hazariah, Abdul Hamid (2024)
As a Muslim and a researcher, it is crucial to ensure that our research ethics framework aligns with religious principles and cultural norms. It is our responsibility not only to pursue knowledge and publication but also to ensure that our research does not deviate from the values we hold dear. Ethical research is fundamental to academic credibility and integrity. For a Muslim, this means conducting research that is consistent with Islamic teachings and respects our cultural norms. This is important becauseit upholds dignity and morality, which are core tenets of Islam